Getting cells into shape by calcium-dependent actin cross-linking proteins - Lehne, Franziska; Bogdan, Sven (Frontiers in Cell and Developmental Biology, 2023)
The actin cytoskeleton represents a highly dynamic filament system providing cell structure and mechanical forces to drive a variety of cellular processes. The dynamics of the actin cytoskeleton are controlled by a number of conserved proteins that maintain the pool of actin monomers, promote actin nucleation, restrict the length of actin filaments and cross-link filaments into networks or bundles. Previous work has been established that cytoplasmic calcium is an important signal to rapidly relay information to the actin cytoskeleton, but the underlying mechanisms remain poorly understood. Here, we summarize new recent perspectives on how calcium fluxes are transduced to the actin cytoskeleton in a physiological context. In this mini-review we will focus on three calcium-binding EF-hand-containing actin cross-linking proteins, α-actinin, plastin and EFHD2/Swiprosin-1, and how these conserved proteins affect the cell’s actin reorganization in the context of cell migration and wound closure in response to calcium.